A comparison of the isometric midthigh pull and isometric squat: Intraday reliability, usefulness, and the magnitude of difference between tests - Brady, C. J.; Harrison, A. J.; Flanagan, E. P.; Haff, G.; Comyns, T. M. (International Journal of Sports Physiology and Performance, 2018)
Purpose: To examine the reliability and usefulness of the isometric midthigh pull (IMTP) and isometric squat (ISqT) performed at the same knee and hip angles. The scores produced in each test were compared to determine the magnitude of differences between tests. Methods: Twenty-six male and female athletes (age, 23.6 [4.3] y; height, 1.75 [0.07] m; and body mass, 68.8 [9.7] kg) performed 2 maximal repetitions of the IMTP and ISqT following a specific warm-up. Results: Maximum force, absolute peak force (PF), relative PF, allometrically scaled PF, rate of force development (0-200 and 0-250 ms), and impulse (0-300 ms) were deemed reliable (intraclass correlation coefficient [ICC] =.86 and coefficient of variation [CV] =9.4%) in the IMTP and ISqT based on predetermined criteria (ICC =.8 and CV =10%). Impulse (0-200 and 0-250 ms) was reliable in the ISqT (ICC =.92 and CV =9.9%). Participants produced significantly (P<.05) greater PF and impulse (0-300 ms) during the ISqT compared with the IMTP. When split by sex, female participants produced significantly greater PF (P=.042) during the ISqT, with no significant differences among male participants (P=.245). Both tests are capable of detecting changes in performance in maximum force and absolute PF. Conclusions: Both tests are reliable for non-time-dependent maximal strength measures when measured at the same knee and hip angles. The ISqT may be preferred when coaches want to test an athlete`s true maximum lower-limb strength, especially female athletes.